Peculiarities of the professional activity of the higher school teacher in the conditions of personalization of modern education - Vasilyeva, I. G. (Problems of Engineer-Pedagogical Education, 2018)
The research deals with the peculiarities of the professional activity of the higher education teacher in the conditions of personalization of modern education. The article highlights the elements that ensure the organization and implementation of personalization in the teaching and learning process of higher educational institutions; it is proved that the personalization of the teacher's activity, embodied in the construction of an author’s pedagogical system, is a decisive educational provision for the personalization of the teaching and learning process in higher education. This system, in turn, is based on a well-developed professional self-knowledge of the teacher and is embodied in the practice of professional-pedagogical cooperation with students within the educational process at university. Personalization of educational activities at the current stage of political and social life is one of the global trends in the development of education that orients teaching and learning process towards further development and formation of relations between the participants of the educational process, based on respect for the rights of each person, рreservation and strengthening of their health, self-esteem, and realization of personal potential.